The Association Between Exclusive Breastfeeding and the Occurrence of Stunting Among Children Aged 12-60 Months in Community Health Centers in Yogyakarta City - Eureka Raihan Asqy Dendy; Rachma Greta Perdana Putri; Dewi Yuniasih; Nurcholid Umam Kurniawan (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2024)
Background: Stunting is a condition of chronic malnutrition caused by suboptimal nutritional intake due to prolonged inadequate food consumption. Stunting, also known as being short, indicates a growth failure that occurs both before and after birth. The categorization of stunting based on the World Health Organization's (WHO) standard growth reference is a deficit in length or height for age with a Z-score < -2. Symptoms of stunting usually appear after the golden period of growth (2 years old). One of the contributing factors to stunting in toddlers is an imbalanced food intake. Exclusive breastfeeding is a critical component of nutritional intake to support a child's good nutritional status. It may contribute to the prevalence of stunting.Methods: This is a quantitative study with a cross-sectional research design. The data collection consists of secondary data from stunting medical record records. The inclusion criteria of the study are children aged 12-60 months with complete data of anthropometric. Exclusion criteria are endocrine disorder, skeletal abnormalities, dysmorphic disorder, chronic disease, history of familial short stature, and constitutional delay of growth and puberty. Analysis of the data using Chi-square.Results: There is a relationship between exclusive breastfeeding and the occurrence of stunting in children aged 12-60 months at the Community Health Centre in Yogyakarta City with a p-value of 0.00 (p < 0.05).Conclusion: There is a correlation between exclusive breastfeeding and the occurrence of stunting among children aged 12-60 months in primary healthcare care in Yogyakarta City.